Vibro-acoustic analysis of functionally graded graphene-reinforced nanocomposite laminated plates under thermal-mechanical loads. (1st May 2019) - Xu, Zhichao; Huang, Qibai
Highlights: Vibro-acoustic analysis of FG-GRC plates under thermal-mechanical loads are studied. The distribution pattern of GPLs considers linear and nonlinear types. A coupling effect between temperature and the width to thickness ratio is found. Results provide references for vibration-noise reduction of FG-GRC plates. Abstract: This paper investigates the vibro-acoustic characteristics of functionally graded graphene-reinforced nanocomposite (FG-GRC) laminated plates under thermal-mechanical loads. It is assumed that the graphene nanoplatelets (GPLs) are distributed with random directions but homogeneous dispersion in each layer while the weight fraction of GPLs shows a layer-wise variation along the thickness direction. The material properties are assumed to be temperature-dependent and are estimated through Halpin-Tsai micromechanical model. The governing differential equations are derived based on Hamilton's principle and the third-order shear deformation plate theory (TSDT). The natural frequencies and vibration displacements of a simply supported FG-GRC plate are obtained by employing the Navier method. The acoustic radiation is calculated through Rayleigh integral method. Results show that the vibro-acoustic characteristics of FG-GRC plates are significantly influenced by the distribution pattern, weight fraction, temperature and geometric parameter of the plate. A coupling effect between temperature and the width to thickness ratio of a plate is found when analyzing the influence of temperature on vibro-acoustic characteristics of FG-GRC plates.